Experimental study on bond failure characteristics of ribbed CFRP bars embedded in ultra-high-performance concrete - Zhang, Jian; Yang, Chengjun; Ai, Zhicheng; Zhang, Zhi; Ke, Lu; Wu, Xiaoyuan (Frontiers in Materials, 2026)
This study investigates the bond failure mechanism between carbon fiber-reinforced polymer (CFRP) ribs and ultra-high-performance concrete (UHPC) in detail. Strain gauges were externally applied to the surface of CFRP bars in long anchor specimens to analyze in detail the variation law of bond stresses and slips with anchorage position, as well as the distribution differences of anchorage-related variables along the anchorage length under different failure modes. Twelve experimental specimens were subjected to pull-out tests, and the test observations were evaluated based on a theoretical analysis. The results indicate that the failure modes of the specimens mainly included pull-out failure and tensile-fracture failure of the CFRP bars, and the ultimate load was closely related to the anchorage length. The anchorage length of the CFRP bars in UHPC should be 20–30 days for 10 mm bars and 10–20 days for 12 mm bars. The anchorage performance of UHPC was comparable to that of steel-tube anchors, and it demonstrated excellent long-term performance. The bond-stress distribution along the anchorage length was nonuniform. As the anchorage length increased, the high-stress region contracted and the average bond strength decreased. Moreover, the relative slip decreased nonlinearly along the anchorage length, and the slip difference between the loading end and free end increased progressively with increasing load.